IN VITRO ABSORPTION STUDY OF CARBAMAZEPINE SOLID DISPERSION USING EVERTED GUT SAC METHOD - Thakur, Nishant; Thakral, Sunil; Goswami, Manish; Ghaie, Pankaj; Thakur, Amit; Mangal, Mohit (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2013)
The oral Bioavailability of BCS (Bio Pharmaceutical Classification System) class II drug with poor solubility and reasonable permeability is limited by drug dissolution. In order to improve the aqueous solubility of the drug and dissolution of thedrug, the solid dispersion was prepared and evaluated for its absorption in intestine using modified everted gut sac method. The solid dispersion of carbamezepine (CBZ) was prepared using polaxomer and guargum by kneading method. The CBZ and CBZSD (Solid Disposisi) shows 2.329% and 3.948% drug absorption, respectively. The data show that solid dispersion increase the absorption of the CBZ in CBZ-SD is more than 70% in comparison to pure CBZ. The increase in CBZ solubility of the SD could be attributed to several factors such as improved wettability, local solubilization, drug particle size reduction and crystalline or, interstitial solid solution reduction.Â Key words: Everted gut sac method, solid dispersion, absorption, solubility